2021
DOI: 10.1002/adtp.202100110
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dual Receptor Enhanced Pre‐Targeting Strategy—A Novel Promising Technology for Immuno‐Positron Emission Tomography Imaging

Abstract: Positron emission tomography (PET) imaging has become an important diagnostic tool. Various pre‐targeting systems have been reported to address limitations associated with traditional immuno‐PET. However, the application of these mono‐receptor based pre‐targeting (MRPT) strategies is limited to non‐internalizable antibodies, and the tumor uptake is usually much lower than that in the corresponding immuno‐PET. To circumvent these limitations, the first dual‐receptor enhanced pre‐targeting (DRPT) system is devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…(D) DRPT leads to greatly enhanced tumor uptake compared with MRPT. Adapted with permission from ref . Copyright 2021 John Wiley and Sons.…”
Section: Pretargeting Strategy For Radiolabelingmentioning
confidence: 99%
See 2 more Smart Citations
“…(D) DRPT leads to greatly enhanced tumor uptake compared with MRPT. Adapted with permission from ref . Copyright 2021 John Wiley and Sons.…”
Section: Pretargeting Strategy For Radiolabelingmentioning
confidence: 99%
“…Several studies reported that tetrazine analogues bearing various imaging modules, such as fluorescent molecules or radionuclides, were coupled with antibody macromolecules (THIO-MAB, huA33) modified with TCO in order to study the in vivo pretargeting strategy (Figure A,B), , while the modification of small molecules with TCO was applied through the incorporation of 18 F-labeled Tz into the small molecule-based radioactive product by Tz/TCO-based pretargeting for detecting hypoxia level (Figure C) . Moreover, Lu et al developed a metabolic pretargeting strategy by conjugating azido sugars with 64 Cu-labeled DBCO tracer using SPAAC reaction for cytotoxic T lymphocytes (CTLs) imaging, whereas a dual-receptor enhanced pretargeting (DRPT) strategy was first reported by the use of IEDDA reaction . The authors investigated the in vivo performance of DRPT targeting EGFR and integrin α v β 3 and then suggested that this DRPT strategy is suitable to radiolabel peptides and small molecules or internalize mAbs to provide higher tumor uptake of radionuclides and relatively increased tumor specificity (Figure D).…”
Section: Pretargeting Strategy For Radiolabelingmentioning
confidence: 99%
See 1 more Smart Citation